2019
DOI: 10.1136/bmjopen-2019-032574
|View full text |Cite
|
Sign up to set email alerts
|

Association between potentially inappropriate medications at discharge and unplanned readmissions among hospitalised elderly patients at a single centre in Japan: a prospective observational study

Abstract: ObjectiveTo determine the prevalence of potentially inappropriate medication (PIM) use at admission and discharge among hospitalised elderly patients and evaluate the association between PIMs at discharge and unplanned readmission in Japan.DesignA prospective observational study conducted by using electronic medical records.ParticipantsAll consecutive patients aged 65 years or older who were admitted to the internal medicine ward were included. Patients who were electively admitted for diagnostic procedures we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
17
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 70 publications
7
17
3
Order By: Relevance
“…Furthermore, our study demonstrated that there is also a significant association between PP and PIM use, which is supported by previous reports [8,[20][21][22][23][24][25][26][27]. The frequency of elderly PIM(+) patients in Japan varies from 22.9% to 67.3% [8,22,23,27,31,35,68,71,72] because of different study populations and settings, different definitions of PIMs, or different timings of the investigation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, our study demonstrated that there is also a significant association between PP and PIM use, which is supported by previous reports [8,[20][21][22][23][24][25][26][27]. The frequency of elderly PIM(+) patients in Japan varies from 22.9% to 67.3% [8,22,23,27,31,35,68,71,72] because of different study populations and settings, different definitions of PIMs, or different timings of the investigation.…”
Section: Discussionsupporting
confidence: 88%
“…Lastly, 64.1% and 56.3% patients had polypharmacy and at least one PIM, respectively, but these percentages may be difficult to compare to the previous reports, because we excluded individuals admitted for an emergency or unable to self-medicate. In previous studies which examined individuals using PP and PIMs, it is likely that the incidence rate of unplanned re-admissions and advanced cognitive impairment are associated with PP and PIMs [67,72]. Furthermore, we did not examine the administration period of the combined use of multiple antithrombotic agents, which may have been overestimated in the percentage of PIMs.…”
Section: Discussionmentioning
confidence: 98%
“…Of these, 103 articles were excluded, mainly because studies reported a different outcome of interest ( n = 58). The final screening identified 63 studies 33–95 suitable for inclusion in this review (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Beers and STOPP criteria address potentially inappropriate medications (PIMs), while START criteria discuss potential prescribing omissions (PPOs). The prevalence of PIP is quite high in older adults, and it is well established that PIP increases the incidence of ADRs and drug related hospitalization in this population [ 4 , 5 ]. Hospital admissions should provide a good incentive for HCPs to optimize medications of hospitalized patients.…”
Section: Introductionmentioning
confidence: 99%